2020
DOI: 10.1186/s12879-020-04972-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of viral load dynamics and CD4 cell count progression in an antiretroviral naive cohort: using a joint linear mixed and multistate Markov model

Abstract: Background: Patients infected with HIV may experience a succession of clinical stages before the disease diagnosis and their health status may be followed-up by tracking disease biomarkers. In this study, we present a joint multistate model for predicting the clinical progression of HIV infection which takes into account the viral load and CD4 count biomarkers. Methods: The data is from an ongoing prospective cohort study conducted among antiretroviral treatment (ART) naïve HIV-infected women in the province o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 56 publications
(64 reference statements)
1
14
0
Order By: Relevance
“…An increased current CD4 + T-cell count in response to ART was observed among women with educational status of certificate and above compared to illiterate women. Similarly, participants with a high educational level had good immunological recovery, and are less prone to comorbidities associated to HIV infection in the studies conducted in KwaZulu-Natal, South Africa, 48 and in India. 49 This might be due to the fact that education may help HIV positive women be aware of the importance of early identification of their status of HIV/AIDS.…”
Section: Discussionmentioning
confidence: 87%
“…An increased current CD4 + T-cell count in response to ART was observed among women with educational status of certificate and above compared to illiterate women. Similarly, participants with a high educational level had good immunological recovery, and are less prone to comorbidities associated to HIV infection in the studies conducted in KwaZulu-Natal, South Africa, 48 and in India. 49 This might be due to the fact that education may help HIV positive women be aware of the importance of early identification of their status of HIV/AIDS.…”
Section: Discussionmentioning
confidence: 87%
“…The result was also consistent with the previous research. 15 In joint analysis, AIDS clinical stage, weight, and hemoglobin level were significantly positively associated with CD4 cell count but had a negative association with TB status. In addition, one-way interaction terms (time * educational level) were also associated with both outcomes, and consistent with the previous study.…”
Section: Discussionmentioning
confidence: 91%
“…In this study, patients who seroconverted during the HIV uninfected stage of CAPRISA 002 and other CAPRISA 004 and 008 trials [19,20], were enrolled into the acute HIV Infection phase, and then followed-up during chronic infection and on cART. Further information about these ongoing prospective HIV cohort studies, including women's eligibility criteria, were reported in [18,21,22]. Finally, two hundred and nineteen (219) participants were included in the study.…”
Section: Study Populationmentioning
confidence: 99%
“…The prognostic factors include (1) cART initiation, (2) demographics: age, marital status, educational level, and sex under the influence of alcohol; (3) OI: hypertension and tuberculosis; (4) clinical parameters: WBC components (neutrophils, lymphocyte count, monocytes, eosinophils count, and leucocyte count), Blood chemistry (sodium, chloride, calcium, ALT, AST, total protein and LDH), RBC parameters (Hb, RDW, MCH, MCV, MCHC, and hematocrit) (5) QoL domain scores. Detailed information about the above-mentioned covariates was given in [21,22,24].…”
Section: Variables and Measurementsmentioning
confidence: 99%